Analisis Pola Komunikasi Orang Tua dan Anak dalam Film “The Sound of Music” - Ramadhani, Andara Nayla; Saleh, Amiruddin; Zahira, Harvia Atika (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Film is a cultural representation medium that reflects the dynamics of family relationships, including communication patterns between parents and children. This study aims to analyze the representation of parent-child communication patterns in the film "The Sound of Music" and their relevance to real-life parenting practices. The study used a descriptive qualitative approach, with the Family Communication Types theory and the SMCRE Model as the basis for analysis. Data were collected through observation of scenes in the film and in-depth interviews with two purposively selected informants: an academic in the field of communication psychology and a parenting practitioner. The data were analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that communication patterns that were initially authoritarian and monopoly-oriented evolved into more open, dialogic, and equality-oriented patterns. These changes are demonstrated by increased openness in conveying messages, children’s involvement in interactions, and the creation of more empathetic relationships between parents and children. These findings emphasize the importance of dialogic and empathetic communication in building healthy family relationships and contribute to the development of family communication studies and parenting practices.